2021
DOI: 10.1038/s41598-021-98873-1
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessels modifications in acute and post-COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 primarily affecting the respiratory system which can damage vessels walls virtually in any body district. Changes affecting retinal vessels are a good marker for systemic vascular alterations. This study investigated retinal vessels during the acute phase of COVID-19 and after patients recovery. Fifty-nine eyes from 32 COVID-19 patients and 80 eyes from 53 unexposed subjects were included. Mean arteries diameter (MAD) and mean ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
2
21
0
4
Order By: Relevance
“…The more significant impact on venular diameter could reflect higher compliance or a different expression of inflammatory or ACE-2 receptors in the venular vessel wall. Similar vascular alterations were observed in the retina of patients recovered from the COVID-19 [ 13 , 26 ]; moreover, vessel dilatation was also observed in the lungs of patients with the COVID-19 pneumonia [ 24 ], which could indicate SARS-CoV-2-induced vascular remodeling and angiopathy. Even though the measured differences in our study are small, especially in the MAD, they are clearly visible in the fundus photographs.…”
Section: Discussionmentioning
confidence: 58%
“…The more significant impact on venular diameter could reflect higher compliance or a different expression of inflammatory or ACE-2 receptors in the venular vessel wall. Similar vascular alterations were observed in the retina of patients recovered from the COVID-19 [ 13 , 26 ]; moreover, vessel dilatation was also observed in the lungs of patients with the COVID-19 pneumonia [ 24 ], which could indicate SARS-CoV-2-induced vascular remodeling and angiopathy. Even though the measured differences in our study are small, especially in the MAD, they are clearly visible in the fundus photographs.…”
Section: Discussionmentioning
confidence: 58%
“…Balance and gait may be assessed and compared with age-based norms. For patients with changes in visual acuity or eye pain, a low threshold for a post-COVID-19 retinal examination seems reasonable given that the eyes are known to have ACE 2 and such examinations can be a window into microvascular alterations affecting the whole body 76 , 77 .…”
Section: Considered Approach To the Evaluation Of Patients With Long ...mentioning
confidence: 99%
“…By measuring sublingual microcirculation for vessels smaller than 20 μm in 12 severely ill COVID-19 patients, Damiani et al [ 188 ] found an inverse correlation between the plasma level of D-Dimer, the perfused vessel density, and the pO2/FiO2 value [ 189 ]. In that study, the D-Dimer plasma level ranged between 717 and 5536 ng/mL.…”
Section: How Sars-cov-2 Infection Of the Nose Leads To Ards Cardiac A...mentioning
confidence: 99%